Oral Health: Work Process and Interdisciplinarity - Danilson Ferreira Cruz; Rodrigo Pinheiro de Toledo Vianna; Luiz Medeiros Araujo Lima-Filho; Daniele Gomes da Silva (Association of Support to Oral Health Research (APESB), 2023)
Objective: To contribute to the debate about tools that favor the organization of the health work process and its interface with interdisciplinary practices. Material and Methods: We opted for a textual construction based on more specific publications on the field of oral health care. Results: The matrix support is configured as a method of inter-professional activity in co-management that aims to favor the qualification of the health care network. From this perspective, it is an interdisciplinary practice capable of integrating two or more areas of knowledge for a better performance of the actors involved in a given organizational and decision-making process, whether in the clinical or health management scope. Conclusion: Matrix support is an essential tool for the practice of managing health services and amplifying interdisciplinary actions.